The shape of Inca history : narrative and architecture in an Andean empire - Niles, Susan A. (University of Iowa Press, 1999)
In The Shape of Inca History, Susan Niles considers the ways in which the Inca concept of history informed their narratives, rituals, and architecture. Using sixteenth-century chronicles of Inca culture, legal documents from the first generation of conquest, and field investigation of architectural remains, she strategically explores the interplay of oral and written histories with the architectural record and provides a new and exciting understanding of the lives of the royal families on the eve of conquest. Niles focuses on the life of Huayna Capac, the Inca king who ruled at the time.